Prime Suspect 7: The Final Act - Martin, Philip; Court, Julian; Mirren, Helen; Tompkinson, Stephen; Greenwood, Laura
Helen Mirren returns for the final time as Jane Tennison in the long-awaited "Prime Suspect 7". Retirement looms for Detective Superintendent Tennison, but as her career draws to a close, the body of a missing schoolgirl is found, and the hunt for her killer begins. However, as Jane and her colleagues work to identify their prime suspect, the emotional fallout from the murder begins to take its toll on the battle-scarred detective. As the investigation gets underway, Jane is not only dealing with the imminent death of her father, but also an addiction to alcohol which she is desperately trying to keep hidden. There are plenty of twists and turns as Jane confronts her toughest challenge yet: herself, as the popular award-winning series reaches its devastating finale. [www.imdb.com]